POPULASI DAN SERANGAN LARVA Batocera hercules Boisduv (COLEOPTERA: CERAMBYCIDAE) PADA TANAMAN PALA DI KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - Ruknindi D.L Mamonto D.L Mamonto; Moulwy Frits Dien; Jimmy Rimbing (Universitas Sam Ratulangi, 2017)
ABSTRACTNutmeg plant is a superior plant of plantation sub-sector of North Sulawesi Province. Basically nutmeg plants are still a source of income farmers at the center of nutmeg production in North Sulawesi. In the development of plants Pala problem faced by farmers is borer stem borer Batocera Hercules. This study aims to determine the population and attack of B. hercules, on nutmeg plants in Kauditan District of North Minahasa Regency. The research used survey method on nutmeg plantation in Kauditan District of North Minahasa Regency. Servey result set three villages as sample location that is Karagesan village, Treman village and Watudambo village.Determination of sample plants was done randomly by selecting each of 20 trees in each village. Observation and sampling is done 4 times with interval once a week. Thus, the total sample crop at each sample/village location is 80 trees. To avoid double observation, the observed plants are marked at the base of the stem and are not observed again.The results showed that from 80 sample plants observed in each village in Kauditan District of North Minahasa Regency, the largest larvae population was found in the Karegesan village ie as many as 38 heads, then Treman village 7 and Watudambo Village 2. The highest percentage of affected plants was found in Keregesan Village which reached an average of 60.00%, then Treman village 26.25% and Watudambo Village 15.00%. The highest level of damage to the crop was found at the site of Karegesan village which reached an average of 2.11 holes / trees, Treman village averaged 0.37 hole / tree, Watudambo village on average 0.16 hole / tree.Keywords : Plant Nutmeg, Population of larva, Batocera hercules